The Effect of the Interaction between the Use of the Improve Strategy in Teaching Mathematics and Achievement Levels on the Acquisition of Algebraic Concepts and Habits of Mind among Tenth Grade Students in Oman (Journal Of Educational and Psychological Researches, 2022)
The current study aims to investigate the effect of the interaction between the use of the improve strategy in teaching mathematics and the level of academic achievement on the acquisition of algebraic concepts and habits of mind among tenth-grade students in Oman. The study adopted the experimental method, based on a quasi-experimental design with two groups: experimental and control groups and pre-post-measurement. The study sample consisted of (28) 10th-grade students as an experimental group and 26 of 10th-grade students as a control group in Al-Tufail bin Amr School in South Al Batinah. The differences in the pretest and posttest gains were analyzed using mean, standard deviation, ANCOVA, t-test, effect size (eta-square), and two-way analysis of variance. There was a significant difference at (α = 0.05) between the mean of the experimental and control group students in the post-application of both the Algebraic Concepts Test and the Habits of Mind scale in favor of the experimental group. The study concluded with a set of important recommendations.